2017
DOI: 10.1038/s41467-017-01117-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 shapes the enhancer landscape of cancer cells in response to chronic immune signaling

Abstract: Inflammation influences cancer development, progression, and the efficacy of cancer treatments, yet the mechanisms by which immune signaling drives alterations in the cancer cell transcriptome remain unclear. Using ChIP-seq, RNA-seq, and GRO-seq, here we demonstrate a global overlap in the binding of tumor-promoting p53 mutants and the master proinflammatory regulator NFκB that drives alterations in enhancer and gene activation in response to chronic TNF-α signaling. We show that p53 mutants interact directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 40 publications
(38 reference statements)
9
81
0
Order By: Relevance
“…Previous reports had already shown that these oncogenic p53 proteins bind RelA like p53 wt. 32 These data suggest that oncogenic versions of p53 that are defective in their DNA binding might retain their ability to interact with RelA and, consequently, influence the expression of RelA target genes by enhancing the DNA binding of NF- κ B, even when nuclear RelA levels are low.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous reports had already shown that these oncogenic p53 proteins bind RelA like p53 wt. 32 These data suggest that oncogenic versions of p53 that are defective in their DNA binding might retain their ability to interact with RelA and, consequently, influence the expression of RelA target genes by enhancing the DNA binding of NF- κ B, even when nuclear RelA levels are low.…”
Section: Resultsmentioning
confidence: 92%
“…31,32 We first tested whether the entire p53 protein is necessary or if one particular structural domain of p53 is sufficient to enhance recombinant rBac-RelA:DNA binding. EMSA analysis revealed that the p53 DNA binding domain (DBD) is effective in stimulating the DNA binding activity of RelA, although the full length protein appeared to be most effective (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of mutant p53 to establish an inflammatory tumor microenvironment is mainly dependent on a functional interaction with NF-κB. In fact, mutant p53 has been shown to promote an efficient and prolonged NF-κB transcriptional activity in various cancer cells stimulated with TNFα, resulting in immune cell infiltration and inflammation [158][159][160][161]. In this way, it has been demonstrated that the inflammatory stimulus led by mutant p53 increases the incidence of invasive colon carcinoma in a mouse model of chronic colitis [160].…”
Section: Stimulation Of Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…These studies support the existence of different mechanisms induced by mutant p53 proteins to modulate the expression of secreted inflammatory cytokines in order to sustain an inflammatory tumor microenvironment, thus potentially contributing to promote oxidative stress and increased cancer aggressiveness. [110,117,118,120,121] R175H, R248W, R273H NF-kB Lung, pancreatic, breast and colon cancer [158][159][160][161][162] R175H, R281G, R273H Cytokines Lung, breast, pancreatic and colon cancer [157,164,165] R175H, R273H PGC1-α Lung, colon and pancreatic cancer [8,137] R175H, R280K, R273H NRF2 Colon carcinoma, oesophageal adenocarcinoma, lung and breast cancer [133][134][135] R175H, R273H AMPK Pancreatic and breast cancer [8,89,110] R175H, R248H, R273H SESNs Breast and pancreatic cancer [8,89] R175H, R273H UCP2 Lung, pancreatic and breast cancer [8] R175H, R273H GSH Oesophageal adenocarcinoma, pancreatic and breast cancer [128,135] R175H, R273H Autophagy Lung carcinoma, pancreatic and breast cancer [89]…”
Section: Stimulation Of Pro-inflammatory Cytokinesmentioning
confidence: 99%